الفعالية الصّادة لمستخلصات الطحلب الأسمر Stypopodium zonale تجاه بعض الجراثيم الممرضة - زينب اسمهان; ابراهيم مازن (Latakia University Journal -Biological Sciences Series, 2019)
Ethanol, methanol, chloroform and acetone extracts of Stypopodium zonale. Were tested for antibacterial activity by disk diffusion method. Studied algae was collected from studies coast in lattakia During the summer of 2014. Pathogenic bacteria were obtained from Al- Assad hospital laboratory in lattakia, which are Streptococcus faecalis, Staphylococcus aureus as gram-positive bacteria, Pseudomonas aeruginosa, Klebseilla sp., Escherishia coli as gram-negative bacteria. The study results showed effective inhibition of chloroform and acetone extracts against Streptococcus faecalis and Staphylococcus aureus, also it showed an effectiveness of ethanol extract against Staphylococcus aureus only, While methanol extracts have not shown any effectiveness against any tested bacteria. As for Gram-negative bacteria did not show any efficancy at all tested extracts. Diameters of inhibiting rings also showed a marked increase according to increase the concentration of extract. Results indicate that the algae has effective substances with antibacterial activity Against isolated Gram-positive pathogenic bacteria, And it can be a source of new antibiotics used to treat bacterial infections in the future. اختبرت فعالية مستخلصات الإيتانول والميتانول والكلورورفورم والأسيتون لطحلب الـ Stypopodium zonale للتحقق من قدرتها الصادّة للجراثيم بطريقة الانتشار في الأغار باستخدام القرص المفرد. جُمعت عينات الطحلب من المياه البحرية لشاطئ شاليهات الدراسات العليا في مدينة اللاذقية خلال صيف عام 2014, وتم الحصول على الجراثيم الممرضة من مختبر مستشفى الأسد الجامعي في اللاذقية وهي: Staphylococcus aureus, Streptococcus faecalis جراثيم موجبة الغرام, Escherichia coli, Klebseilla sp., Pseudomonas aeruginosa جراثيم سالبة الغرام. أظهرت نتائج الدراسة فعالية تثبيطية لمستخلصات الكلوروفورم والأسيتون تجاه الجراثيم Streptococcus faecalis وَ Staphylococcus aureus, ولمستخلص الإيتانول تجاه جراثيم Staphylococcus aureus فقط, بينما لم تبد مستخلصات الميتانول أية فعالية تجاه أي نوع من الجراثيم المستخدمة, لوحظ أيضاً عدم وجود فعالية عند جميع المستخلصات السابقة تجاه الجراثيم سالبة الغرام المستخدمة. كما بيّنت أقطار حلقات التثبيط زيادة ملحوظة بزيادة تركيز المستخلص. تشير النتائج إلى امتلاك طحلب الـ Stypopodium zonale لمواد فعالة حيوياً ذات قدرة تثبيطية تجاه الجراثيم الممرضة المعزولة موجبة الغرام ويمكن أن تكون مصدراً لصادّات حيوية جديدة تستخدم في علاج الإنتانات الجرثومية في المستقبل.